2014
DOI: 10.1093/mnras/stu1647
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet background fluctuations with clustered sources

Abstract: We develop a count-in-cells approach to the distribution of ultraviolet background fluctuations that includes source clustering. We demonstrate that an exact expression can be obtained if the clustering of ionising sources follows the hierarchical ansatz. In this case, the intensity distribution depends solely on their 2-point correlation function. We show that the void scaling function of high redshift mock quasars is consistent with the Negative Binomial form, before applying our formalism to the description… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…As mentioned previously, Dixon et al (2014) showed that the impact of quasar clustering on ionizing background fluctuations was likely small. Recent work by Desjacques et al (2014) suggests that clustering could have a significant effect on background fluctuations at z ∼ 3 if the mean free path is comparable to the correlation length of quasars, r ξ ∼ 15 Mpc. The average mean free path in our simulations is substantially larger than this for the redshifts we are interested in (λ mfp > ∼ 25 Mpc), but it is reasonable to expect that the addition of mean free path fluctuations would enhance the effect of clustering to some degree.…”
Section: (Iii) Clustering Of Sources and Absorbersmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously, Dixon et al (2014) showed that the impact of quasar clustering on ionizing background fluctuations was likely small. Recent work by Desjacques et al (2014) suggests that clustering could have a significant effect on background fluctuations at z ∼ 3 if the mean free path is comparable to the correlation length of quasars, r ξ ∼ 15 Mpc. The average mean free path in our simulations is substantially larger than this for the redshifts we are interested in (λ mfp > ∼ 25 Mpc), but it is reasonable to expect that the addition of mean free path fluctuations would enhance the effect of clustering to some degree.…”
Section: (Iii) Clustering Of Sources and Absorbersmentioning
confidence: 99%
“…Quasars are randomly placed in a cosmological volume 500 Mpc on a side from z = 4 to z = 2.5 following the Hopkins et al (2007) B-band quasar luminosity function (QLF). By placing quasars randomly we neglect their clustering; the effect of quasar clustering on fluctuations in the ionizing background is likely small (Dixon et al 2014) but could play a role when the mean free path is very short (Desjacques et al 2014; see Section 5.1). The ionizing spectrum of each quasar is determined by first converting the B-band luminosity to the luminosity at the H I ionizing edge with the constant conversion factor from Hopkins et al (2007) and assuming that the spectrum at ν > νH I is a power law Lν ∝ ν −α Q with αQ = 1.6 in agreement with Telfer et al (2002) and consistent with the recent estimate by Lusso et al (2015).…”
Section: A Numerical Model Of the He II Ionizing Backgroundmentioning
confidence: 99%
“…This power-law behavior is known to arise from the nearest neighbor [40]. Similarly, bearing in mind that P (h 2 ) = P (h)/h, the large-h asymptotic scaling (21) implies…”
Section: The Importance Of Interferencesmentioning
confidence: 89%
“…been considered in the past by refs. [41][42][43], and the upshot is that, if the number of sources is finite, then the probability of g 2 rel being higher than h is ∼ h −3 , for large h. Thus,…”
Section: Jcap02(2021)049mentioning
confidence: 99%